Perjuangan Perempuan Dalam Novel Tentang Kamu Karya Tere Liye : Kajian Feminisme - Romadhoni, Hendra; Islam, Muhammad Hifdil; Hamdiah, Magfirotul (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
the practical level there are still many things that are not in accordance with what has been agreed at the theological level. The novel About You by an Indonesian writer with the pen name Tere Liye is the object of research. In this novel, it examines the values in literary works, such as the value of literary feminism which examines women's gender equality. The type of research used in this research is library research (library research) with qualitative descriptive data presentation. The story about Sri Ningsih can be seen as an illustration of the concept of feminism which highlights women's struggle in facing rigid gender norms and traditionally assigned roles in society. In the context of feminism, Sri Ningsih is a clear example of a woman who challenges gender stereotypes by doing work that is usually considered men's work, such as looking for sea cucumbers, shellfish and sea urchins in the oceanKeywords: Women's Struggle, Faminism Studies